(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Despite the free access to and consumption of quality drinking water, which is essential for human well-being, both natural occurrences and anthropogenic activities worldwide have significantly compromised the quality of drinking water, thereby reducing its availability and safety. This study examined the pollution levels in drinking water and the associated health risks in selected communities of Ondo State, Nigeria. One hundred water samples were obtained from drinking water sources in ten selected riverine communities in Ondo South. The evaluation of physicochemical parameters, toxic metals, and microbial load was conducted in accordance with APHA, USEPA IRIS, and WHO guidelines. The results indicated that concentrations of toxic metals and physicochemical parameters exceeded the permissible limits set by WHO and USEPA IRIS. Gram staining and IMViC tests verified the presence of fecal coliforms, indicating fecal contamination against the WHO standards. Chronic Daily Intake (CDI) ranks as follows: Babies > Children > Adults, whereas the cancer risk hierarchy is As > Cd > Cr. The Hazard Quotient is in the order Pb > As > Cr > Cd, significantly surpassing the permissible limit of less than 1. The analysis concludes that drinking water in the study areas presents a risk for diseases such as diarrhea, cholera, and cancer. The elevated water pollution in these study areas results from the presence of chemicals, specifically heavy metals, and microbial contaminants originating from household waste.